Hubungan Motivasi Dengan Perilaku Orang Tua Dalam Pencegahan Kejang Demam Berulang Pada Balita Di Ruang Asoka RSUD dr. Murjani Sampit - Karmitasari Yanra Katimenta; Agustina Nugrahini; Mida Kartika Wati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Toddlers are children in the age range of 0-5 years old. The childhood period is the most vulnerable to diseases. Febrile seizures are often encountered in toddlers, where the body temperature rises suddenly and becomes a triggering factor for seizures. Based on the frequently occurring phenomenon, many parents do not know how to handle seizures, and when a child has a fever, it is not handled properly, such as not immediately applying warm compresses to the child, not giving fever-reducing medicine. Therefore, some parents still lack strong motivation to prevent febrile seizures. The research aims to analyze the relationship between motivation and parental behavior in preventing recurrent febrile seizures in toddlers in the Asoka Room of RSUD dr. Murjani Sampit. This is a quantitative study, correlational design with a cross-sectional approach, and total sampling technique. The sample consists of 54 parents. Data collection is done using two questionnaires: a motivation questionnaire and a behavior questionnaire, using the Spearman rank statistical test. The research results obtained a p-value of 0.000 <0.05, indicating a relationship between motivation and the behavior of preventing recurrent seizures in toddlers in the Asoka Room of RSUD dr. Murjani Sampit. The correlation coefficient value is 0.553, meaning it has a strong positive relationship. The conclusion of this study is that there is a relationship between motivation and parental behavior in preventing recurrent seizures in toddlers in the Asoka Room of RSUD dr. Murjani Sampit.